Lohnentwicklung im Lebenszyklus - Robert Orlowski; Regina T. Riphahn (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2011)
– This paper summarizes the findings of studies which investigate the determinants of wages in Germany, using data of the German Socioeconomic Panel (GSOEP). The empirical analyses apply least squares estimates as well as the estimators developed by Altonji and Shakotko, Rev. Econ. Stud. 54, 437 (1987) and Topel, J. Polit Econ. 99(1), 145 (1991). These estimators reduce the endogeneity of indicators of specific and general labor market experience. The studies focus on the heterogeneity in wage determinants in the private and the public sector, in East and West Germany, for men and women, as well as in large versus small firms. Among the most interesting results, we find clear differences in returns to experience between East and West and by employer size.
Keywords: J21; J24; 330; Lohnentwicklung; Lebenslauf; Berufsverlauf; Lohnstruktur; Heterogenität; Privatwirtschaft; öffentlicher Dienst; erwerbstätige Frauen; erwerbstätige Männer; Großunternehmen; Kleinbetrieb; Unternehmensgröße; regionaler Vergleich; Berufserfahrung; Betriebszugehörigkeit; Humankapitalansatz; Bildungsertrag; Einkommenseffekte; Lohnhöhe; Ostdeutschland; Westdeutschland; Bundesrepublik Deutschland